2019
DOI: 10.3389/fmars.2019.00630
|View full text |Cite
|
Sign up to set email alerts
|

The Decreasing Availability of Settlement Surfaces Affects the Transition From Larvae to Early Recruitment of the Scallop Argopecten purpuratus Through El Niño and La Niña Episodes

Abstract: Frontiers in Marine Science | www.frontiersin.org October 2019 | Volume 6 | Article 630 Avendaño et al.Larval Ecology of Argopecten purpuratus that, whether EN-LN-driven thermal shifts had an effect on the larval settlement of A. purpuratus, it is masked by the strong and continuous reduction in the availability of Rhodymenia spp. as a settlement surface. This reduction may have consequences for the stability of natural stocks of A. purpuratus in Chile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…The settlement of Argopecten purpuratus Lamarck (1819) from hatchery reared larvae, shows similar survival (6.31-24.94%) as observed in other scallops (Avendaño-Herrera et al, 2002). Though no causable effects were discussed for the related rates, for A. purpuratus, a positive correlation between temperature and the high concentration of larvae in water column are significant predictors for most successful survival rates for this species (Avendaño et al, 2019). The settlement rate in Mimachlamys varia Linnaeus (1758) ranging from 17.7 to 32.3% were described (De La Roche et al, 2005), being the best survival of spat found in larger sheltered areas at low luminosity in the inner center with spat attaching one on top of another.…”
Section: Discussionmentioning
confidence: 73%
“…The settlement of Argopecten purpuratus Lamarck (1819) from hatchery reared larvae, shows similar survival (6.31-24.94%) as observed in other scallops (Avendaño-Herrera et al, 2002). Though no causable effects were discussed for the related rates, for A. purpuratus, a positive correlation between temperature and the high concentration of larvae in water column are significant predictors for most successful survival rates for this species (Avendaño et al, 2019). The settlement rate in Mimachlamys varia Linnaeus (1758) ranging from 17.7 to 32.3% were described (De La Roche et al, 2005), being the best survival of spat found in larger sheltered areas at low luminosity in the inner center with spat attaching one on top of another.…”
Section: Discussionmentioning
confidence: 73%
“…The main cause seems to be genomic abnormalities related to stock origin but could be also associated with environmental contaminations or a sign of disseminated neoplasia disorder 9 , 10 . These events are not exclusive to mussel species and also affect Pectinids 11 13 and cockles 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, retention is favoured by the coastal topography and the occurrence of predominantly south‐westerly winds, which generate a northward‐directed residual current, causing gyre currents of approximately 5 km radius in the eastern sector of the bay, with residence times varying from 4 to 12 days in the summer and from 2 to 24 days in the winter (Cantillánez Silva, Thouzeau & Avendaño, 2007; Avendaño et al, 2008; Avendaño & Cantillánez, 2008). Additionally, the recruitment of A. purpuratus is strongly influenced by temperature variations associated with El Niño and La Niña climatic events (Avendaño, Cantillánez & Riascos, 2019). These processes modify the circulation of water masses and disturb the upwelling of cold water along the coasts of northern Chile (Escribano & Hidalgo, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, coralline algae induce larval settlement in many invertebrate phyla (Dayton et al, 2000). Studies of the benthos of La Rinconada MR have shown that pre‐recruitment seeds of A. purpuratus are attached to the fronds of the red alga Rhodymenia sp., which is the only biological substrate available on the predominantly fine sandy bottom of the reserve and shows substantial seasonal and interannual variation (Cantillánez, 2000; Avendaño, Cantillánez & Thouzeau, 2017; Avendaño, Cantillánez & Riascos, 2019). Trophic models (ECOPATH and ECOSIM) constructed for the benthic ecosystem of the MR have established that A. purpuratus play an important role in the trophic network, as do red algae ( Rhodymenia sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation